PENERAPAN LOCATION BASED SERVICED (LBS) DALAM PROTOTIPE PENGENALAN RUANGAN DENGAN METODE EXTREME PROGRAMMING - Viktor Handrianus Pranatawijaya (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
Location Based Service (LBS) is a service to provide information that has been created, compiled, selected or filtered by considering the location of users or other people or current mobile devices [1]. It is possible to implement LBS using GPS because mobile devices have GPS services [6]. Based on these services, making an application for room recognition can be done by utilizing the Google Maps API by implementing GIS, LBS, and GPS. Implementation of application with extreme programming methods is carried out in accordance with the stages. In the planning part, an analysis is carried out on the business needs and user stories, in the design, use case diagrams and activity diagrams are made, coding is done by implementing the design using the mobile programming language, and testing is done using black box testing. The application of LBS is carried out when calling the room information page which functions to find the location of the room and displays notifications and room information when the user enters the radius that has been determined in the room data. Determining the radius is very important to do so that the information about the room that is displayed does not overlap with other rooms. This is done to keep the room information displayed to the user only to display information about one room only. Therefore, when determining the radius of the room, it must be determined carefully so that the radius can create a circle that does not intersect with other radius circles. The room information displayed is obtained from data management by the admin through the building management page, rooms, and items. In managing, admins can add, edit, and delete data.